ANALYSIS OF LEGAL SCIENCE'S VIEWS ON THE OBLIGATION OF COMMUNITY GARDEN DEVELOPMENT (PLASMA GARDEN) IN PLANTATION COMPANIES AS A MANDATE OF THE PRINCIPAL AGRARIAN LAW - Juda Deo Silitonga; Maria Kaban; Rosnidar Sembiring (Journal of International Islamic Law, Human Right and Public Policy, 2024)
The obligation to provide plasma plantations is also one of the requirements for obtaining land rights in the form of Cultivation Rights (HGU) by the Company, as stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 7 of 2017 concerning Regulations and Procedures for Determining Cultivation Rights, which in Article 40 letter (k) and Article 41 states: "One of the obligations of HGU Holders is to Facilitate the development of local community gardens of at least 20% (twenty percent) of the land area The HGU application for the surrounding community is in the form of a partnership (plasma) in accordance with the business activity permit from the competent technical agency, and the application for partnership (plasma) land rights is submitted simultaneously with the company's HGU application." To achieve one of the goals of the Republic of Indonesia as stated in paragraph IV of the preamble to the 1945 Constitution of the Republic of Indonesia, namely to advance general welfare, the abundance of palm oil production must be utilized as much as possible for national development strategies, this is carried out from various functions related to economics, ecology and socio-culture. Regulations related to the obligation to facilitate the development of plasma plantations have been amended through Law no. 11 of 2020 concerning Job Creation as amended by Government Regulation in Lieu of Law No. 2 of 2022 which was promulgated through Law no. 6 of 2023 has been adjusted and regulated in more detail in its derivative regulations, namely Government Regulation no. 26 of 2021 concerning the Implementation of the Agricultural Sector and Minister of Agriculture Regulation No. 18 of 2021 concerning Facilitation of the Development of Gardens in Surrounding Communities.